Rancangan Model HAMEMAYU WARASING DESA untuk Pengendalian Multirisiko Penyakit Tidak Menular Berbasis Pemberdayaan Kader Kesehatan di Kalurahan Caturharjo - Rinaldi Muhammad Fauzi; Salsabila Maura Aji; Hadi Sasongko; Zia Adhwaa Nugraha; Nayla Annisa; Happy Okta Bima; Nazira Humayra; Erwanda Candra Mustika; Nandan Aifanisa Hanun (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The high number of non-communicable disease cases is influenced by low public awareness of early detection, limited capacity of health cadres, and a manual recording system. This article aims to develop a HAMEMAYU WARASING DESA model as a multi-risk control strategy for NCDs based on empowering health cadres in Caturharjo Village. The method used is a descriptive-conceptual approach through observation, interviews, and Focus Group Discussions (FGDs). The results of the model development indicate that HAMEMAYU WARASING DESA consists of five main components: PELITA KADER, PITUTUR WARAS, One Stop Service, SI-WARAS, and the integrated NCD Control Card. This model is designed to increase cadre capacity, strengthen public health literacy, facilitate screening, and support the digitalization of risk recording and monitoring.